2020
DOI: 10.1039/d0sc00876a
|View full text |Cite
|
Sign up to set email alerts
|

J-dimer emission in interwoven metal–organic frameworks

Abstract: J-dimer emission is an emergent property that occurs when pairs of ground-state fluorophores associate within multivariate MOFs producing tunable red shifted emission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…To verify our speculation about the ACQ effect in UiO-68-NTMB and UiO-68-NSMB and to improve the quantum efficiency, a mixed-linker strategy was employed, where a nonemissive linker, 2′,5′-dimethyl-[1,1′:4′, 1″-terphenyl]-4,4″-dicarboxylic acid ( d TPDC), was used along with the emissive NTMB and NSMB to increase the distances between the emissive linkers. ,, For d TPDC, its HOMO (LUMO) is much lower (higher) than those of the six emissive linkers; therefore, no charge/energy transfer will occur between d TPDC and the emissive linkers (Figure S5). Mixed-linker MOFs were thus prepared using the same method as for pure linker MOFs (Table S1), where the ratio of L and d TPDC varies from 1:1 to 1:2, 1:5, and 1:10.…”
mentioning
confidence: 99%
“…To verify our speculation about the ACQ effect in UiO-68-NTMB and UiO-68-NSMB and to improve the quantum efficiency, a mixed-linker strategy was employed, where a nonemissive linker, 2′,5′-dimethyl-[1,1′:4′, 1″-terphenyl]-4,4″-dicarboxylic acid ( d TPDC), was used along with the emissive NTMB and NSMB to increase the distances between the emissive linkers. ,, For d TPDC, its HOMO (LUMO) is much lower (higher) than those of the six emissive linkers; therefore, no charge/energy transfer will occur between d TPDC and the emissive linkers (Figure S5). Mixed-linker MOFs were thus prepared using the same method as for pure linker MOFs (Table S1), where the ratio of L and d TPDC varies from 1:1 to 1:2, 1:5, and 1:10.…”
mentioning
confidence: 99%
“… 32 , 33 For instance, it was found that the stiffening of luminophores in networks increases their fluorescence intensity because of decreased vibrational decay. Furthermore, the precise spatial fixation of fluorophores within a lattice can significantly influence the fluorescence properties and lead to interesting effects like J dimer emission 34 or multiemission. 35 , 36 Also, phenomena like charge and energy transfer, known from classical coordination chemistry, were observed.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, different strategies were used to integrate fluorescent moieties into MOFs especially for sensing applications. , For instance, it was found that the stiffening of luminophores in networks increases their fluorescence intensity because of decreased vibrational decay. Furthermore, the precise spatial fixation of fluorophores within a lattice can significantly influence the fluorescence properties and lead to interesting effects like J dimer emission or multiemission. , Also, phenomena like charge and energy transfer, known from classical coordination chemistry, were observed. , In addition to pure ligand-based fluorescence, MOFs containing d 10 ions often exhibit metal-to-ligand (MLCT) and ligand-to-metal charge transfer (LMCT) . Alternatively, fluorophores can be introduced into the pore system, which can lead to interesting emission properties .…”
Section: Introductionmentioning
confidence: 99%
“…32,33 For instance, it was found that the stiffening of luminophores in networks increases their fluorescence intensity because of decreased vibrational decay. Furthermore, the precise spatial fixation of fluorophores within a lattice can significantly influence the fluorescence properties and lead to interesting effects like J dimer emission 34 or multi emission. 35,36 Also, phenomena like charge and energy transfer, known from classical coordination chemistry, were observed.…”
Section: Introductionmentioning
confidence: 99%